2012
DOI: 10.1093/annonc/mds101
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hospital volume and surgical treatment delay on long-term survival after cancer surgery

Abstract: Our findings suggest that the effect of hospital volume and surgical treatment delay on overall survival of cancer patients should be considered in formulating or revising national health policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(182 citation statements)
references
References 26 publications
11
168
3
Order By: Relevance
“…A previous study on the relationship between hospital volume/treatment delay and survival after cancer surgery indicated that improved outcomes were found in patients treated in high volume hospitals [24]. It was reported that many quality-of-care factors may contribute to a better prognosis in high service volume hospitals, including completeness of surgical resection, number of lymph nodes yielded, application of multimodality therapeutic protocol, and better treatment of comorbidities [24]. …”
Section: Discussionmentioning
confidence: 99%
“…A previous study on the relationship between hospital volume/treatment delay and survival after cancer surgery indicated that improved outcomes were found in patients treated in high volume hospitals [24]. It was reported that many quality-of-care factors may contribute to a better prognosis in high service volume hospitals, including completeness of surgical resection, number of lymph nodes yielded, application of multimodality therapeutic protocol, and better treatment of comorbidities [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Also, surgical mortality might be low because the NCC in Korea is a high-volume center. Surgical patients in high-volume hospitals have shown significantly better survival than those in low-to medium-volume hospitals (27). Here, we included only patients who had R0 resection carried out.…”
Section: Discussionmentioning
confidence: 99%
“…travel distance and increased crowding on the other (Distante et al, 2004;Bouche et al, 2008;Stitzenberg et al, 2009;Yun et al 2012). Unfortunately, our data do not include information on comorbidity, which is, however, highly correlated with socioeconomic position and therefore partially adjusted for in the analyses.…”
Section: Timeliness Indicatorsmentioning
confidence: 97%